Hubungan Perilaku Masyarakat dengan Kejadian Diare di Wilayah Rawan Banjir Desa Lembasada Kabupaten Donggala - Marselina, Marselina; Larasati, Rahma Dwi; Vidyanto, Vidyanto; Sari, Nur Fadhilah; Nuriyah, Nur Aini; Nurhalisah, Siti (Universitas Pahlawan Tuanku Tambusai, 2024)
Floods are the most frequent natural disasters and damage the environment. The intensity and frequency of flooding is increasing due to climate change and rainfall as well as rising sea levels. Floods can cause health problems, one of the diseases caused after a flood is diarrhea. This research aims to determine the relationship between community behavior and the incidence of diarrhea in flood-prone areas in Lembasada Village, Donggala Regency. This type of research is quantitative with a cross sectional approach. The number of samples in this study was 90 mothers who had toddlers registered in the Lembasada Community Health Center Work Area. The sampling technique uses positive sampling. The analysis used in this research is the Chi Square analysis test. The results of the study showed that the behavior of using toilets was related to the incidence of diarrhea (p=0.036), the behavior of using clean water (p=1.000), the behavior of washing hands with soap (p=0.929) and the behavior of cooking water (p=0.498) was related to the incidence of diarrhea. The conclusion of this research is that there is a relationship between the behavior of using toilets and the incidence of diarrhea and there is no relationship between the behavior of using clean water, the behavior of washing hands with soap and the behavior of boiling water and the incidence of diarrhea in the Flood Prone Area of ??Lembasada Village, Donggala Regency.